Bioecology of Wild Betta Fish (Betta schalleri) of Bangka Island Waters - Olivia Khanati; Dona Lista; Lindiatika Lindiatika; Ahmad Fahrul Syarif (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2024)
The Betta schalleri is a wild betta fish endemic to Bangka Island which has potential as an ornamental fish. However, the fish’s endangered conservation status is one of the problems for its conservation efforts. The aim of this study was to analyze the Betta schalleri according to its biological and ecological properties. The research method was quantitative descriptive. Parameters measured in this study included fish morphology, fish meristics, water quality and habitat characteristics. The fish samples collected was 15 Betta schalleri. Observations on the physical characteristics of the Betta schalleri were based on morphometric characters, namely: 1) Total Length (TL) (22355.59 mm); 2) Standard Length (SL) (16386.74 mm);3) Head Length (HL) (3912.51 mm); 4) Head Height (HH) (3112.72 mm); 5) and Caudal Height (CH) (4922.29 mm). The meristic characters brought about the following 1) Dorsal Fin (D.II.8); 2) Anal Fin (A.II.24-25); Ventral Fin (V.I-II.4); Pectoral Fin (P.11-12); Caudal Fin (C.13) and Linea Lateralis (LL.31-32). The betta schalleri typically live in peat water, calm and fresh water that tend to be brown in color. The aquatic plants grow in the form of Pandanus sp. and Utricularia sp. In general, Betta schalleri thrive in a pH of 4-5, a temperature from 280C to 310C, and dissolved oxygen of 5.6- 11 mg/l.